Sustainable building services : principles, systems, concepts. - Lenz, Bernhard, ....-; Schreiber, Jürgen, ....-; Stark, Thomas, ....- (Munich : Detail, 2011)
For sustainable operation of buildings, energy-efficient systems for heating, cooling, ventilation and the supply of power are essential. Particularly during building renovations, modifications of the building services allow great savings to be realised at relatively little expense. The book "Sustainable Building Services" explains in compact, easy-to-understand form the most important system concepts and components. It documents how each of the technologies works and shows how they interact in overall concepts. The state of development of technologies of the future such as photovoltaics, heat pumps or solar climate control is also documented. The authors pay special attention to renovation measures and the optimisation of operational processes. 15 current building examples illustrate how building services are individually adjusted to different uses, building sizes and climate zones. The book thus provides both architects and specialist engineers with an important knowledge base for planning energy-efficient buildings.
Keywords: Architectuur; Bouwfysica; Bouwkunde; Duurzaam bouwen; Duurzame energie; Ecologisch bouwen; Energie; Kwaliteitssystemen; Sustainable buildings -- Design and construction